Implementing 'universal' access to antiretroviral treatment in South Africa: a scoping review on research priorities. Issue 6 (8th May 2021) - Myburgh, Hanlie; Reynolds, Lindsey; Hoddinott, Graeme; van Aswegen, Dianne; Grobbelaar, Nelis; Gunst, Colette; Jennings, Karen; Kruger, James; Louis, Francoise; Mubekapi-Musadaidzwa, Constance; Viljoen, Lario; Wademan, Dillon; et al.
Abstract: 'Universal' access to antiretroviral treatment (ART) has become the global standard for treating people living with HIV and achieving epidemic control; yet, findings from numerous 'test and treat' trials and implementation studies in sub-Saharan Africa suggest that bringing 'universal' access to ART to scale is more complex than anticipated. Using South Africa as a case example, we describe the research priorities and foci in the literature on expanded ART access. To do so, we adapted Arksey and O'Malley's six-stage scoping review framework to describe the peer-reviewed literature and opinion pieces on expanding access to ART in South Africa between 2000 and 2017. Data collection included systematic searches of two databases and hand-searching of a sub-sample of reference lists. We used an adapted socio-ecological thematic framework to categorize data according to where it located the challenges and opportunities of expanded ART eligibility: individual/client, health worker–client relationship, clinic/community context, health systems infrastructure and/or policy context. We included 194 research articles and 23 opinion pieces, of 1512 identified, addressing expanded ART access in South Africa. The peer-reviewed literature focused on the individual and health systems infrastructure; opinion pieces focused on changing roles of individuals, communities and health services implementers. We contextualized our findings through a consultative process with a group of researchers, HIV clinicians and programme managers to consider critical knowledge gaps. Unlike the published literature, the consultative process offered particular insights into the importance of researching and intervening in the relational aspects of HIV service delivery as South Africa's HIV programme expands. An overwhelming focus on individual and health systems infrastructure factors in the published literature on expanded ART access in South Africa may skew understanding of HIV programme shortfalls away from the relational aspects of HIV services delivery and delay progress with finding ways to leverage non-medical modalities for achieving HIV epidemic control.